A comprehensive study of clustering a class of 2D shapes - Kaliszewska, Agnieszka; Syga, Monika (Zielona Góra: Uniwersytet Zielonogórski)
The paper is concerned with clustering with respect to the shape and size of 2D contours that are boundaries of cross-sections of 3D objects of revolution. We propose a number of similarity measures based on combined disparate Procrustes analysis (PA) and dynamic time warping (DTW) distances. A motivation and the main application for this study comes from archaeology. The computational experiments performed refer to the clustering of archaeological pottery.
Keywords: shape representation; Procrustes distance; shape similarity; DTW; morphometrics; clustering; Kendall shape theory; typology of archaeological pottery